2020
DOI: 10.3389/fcell.2020.561503
|View full text |Cite
|
Sign up to set email alerts
|

Increased Protein Stability and Interleukin-2 Production of a LATG131D Variant With Possible Implications for T Cell Anergy

Abstract: The adaptor LAT plays a crucial role in the transduction of signals coming from the TCR/CD3 complex. Phosphorylation of some of its tyrosines generates recruitment sites for other cytosolic signaling molecules. Tyrosine 132 in human LAT is essential for PLC-γ activation and calcium influx generation. It has been recently reported that a conserved glycine residue preceding tyrosine 132 decreases its phosphorylation kinetics, which constitutes a mechanism for ligand discrimination. Here we confirm that a LAT mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
2
7
1
Order By: Relevance
“…As seen in Figure 1C , when thymocytes are stimulated with a concentration of 0.62 µg/ml the phosphorylation of PLC-γ1 and LAT tyrosine 136 are increased in mutant mice relative to wild type. This supports previous data generated by our group and others in Jurkat cells ( 12 , 15 ). However, Erk phosphorylation ( Figure 1C ) and Ca 2+ influx generation ( Supplementary Figure 3C ) do not appear to be increased in thymocytes from LAT-G135D mice.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…As seen in Figure 1C , when thymocytes are stimulated with a concentration of 0.62 µg/ml the phosphorylation of PLC-γ1 and LAT tyrosine 136 are increased in mutant mice relative to wild type. This supports previous data generated by our group and others in Jurkat cells ( 12 , 15 ). However, Erk phosphorylation ( Figure 1C ) and Ca 2+ influx generation ( Supplementary Figure 3C ) do not appear to be increased in thymocytes from LAT-G135D mice.…”
Section: Resultssupporting
confidence: 93%
“…It has been previously shown that proper integration of calcium signals with other signaling pathways results in full T cell activation, while unopposed calcium signaling leads to anergy ( 25 , 26 ). Although we have not been able to demonstrate an increase in calcium influxes, previous data obtained in Jurkat cells show that the LAT G135D mutation potentiates PLC-γ1 activation and Ca 2+ responses ( 12 , 15 ). Therefore, it was of interest to analyze whether the LAT G135D mutation increased the percentage of anergic T cells.…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…This cell line may constitute a new tool to untangle molecular events related to the TCR signaling cassette and biology of T cells. Through the lentiviral transfection of J.CaM2 cells, we have recently shown that a mutation of LAT glycine 131 to aspartate increases IL-2 production in response to CD3/CD28 engagement [64]. The new J.CaM1.7 cells may be useful to confirm these data and verify the role of Lck domains or motifs in this behavior.…”
Section: Discussionmentioning
confidence: 81%
“…This slow phosphorylation of LAT Y132 is a feature that had been previously noted (96) but with an unclear basis or significance. Interestingly, the simple substitution of an acidic residue, glutamate or aspartate, at the -1 position (i.e., G131E or G131D) increased the phosphorylation rates of LAT Y132, the recruitment, phosphorylation and activation of PLCg1, and the magnitude and the rate of calcium elevation (50,97). The augmented LAT-PLCg1-calcium pathway resulted in an increase in T cell responses (50).…”
Section: Lat G131 Is An Apparent Tcr Signaling Bottleneck For Tcr Actmentioning
confidence: 99%